Primulina guigangensis (Gesneriaceae): a new species from limestone area in Guangxi, China - Wu, Lei; Zhang, Qiang; Xu, Wei-Bin; Mo, Shui-Song (Phytotaxa, 2012)
Primulina guigangensis, a new species found in the limestone area of Guigang city, Guangxi, China is described and illustrated. It is most similar to Primulina yunfuensis, but can be distinguished from the latter by several distinct characters in calyx, corolla, filament, stigma and phenology. The detailed morphological characters together with illustrations, diagnostic comparisons and habitat etc. are presented.